Establishing Productive Arboriculture to Enhance the Local Economy and Safeguard the Environment in the Lake Toba Region, Silahisabungan District, Dairi Regency, North Sumatra Province - Kaniwa Berliani; Arlen HJ; Nursal; Putri Cahaya Situmorang; Muhammad Zaidun Sofyan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Lake Toba features a diverse array of geological landscapes and rock formations, alongside globally acknowledged cultural and biological variety. The geological diversity of the Lake Toba caldera possesses significant Geological Heritage value. This region possesses significant potential as a premier tourism destination and merits inclusion in a worldwide geopark. A survey in Silahisabungan District identified desolate, landslide-prone regions along the shores of Lake Toba that remain uncultivated. Simultaneously, a significant portion of the region is allocated for ecotourism. Should the tourist site suffer escalating degradation owing to desolation, it is anticipated that the influx of visitors to the Silahisabungan region will likewise diminish. If the community's economic revenue relies exclusively on the tourism industry, the economy would undoubtedly face challenges; therefore, economic income must be derived from several sectors. Consequently, the region urgently requires the implementation of tree planting initiatives, particularly including 1,500 productive tree types. Productive tree seedlings will be cultivated in five villages: Paropo, Paropo I, Silalahi I, Silalahi II, and Silalahi III, located in the Silahisabungan District of Dairi Regency, North Sumatra. The tree planting initiatives are anticipated to yield economic benefits for the community through fruit harvests. This planting initiative would enhance the local economy while reforesting desolate area, hence drawing tourists to Silahisabungan.